The Influence of External Support, Social Capital and Entrepreneurial Attitude Orientation on Social Entrepreneurial Intentions: The Mediating Role of Psychological Capital - Alwehabie, Abdullah (Journal of Ecohumanism, 2025)
A recent development in entrepreneurship, social entrepreneurship (SE) aims to generate social benefit for its recipients. the tools that social entrepreneurs can use to preserve their mental health (MWB), which is crucial for carrying out their social missions. In order to scientifically investigate the predictive values of four categories of resources—personality, external support, and social impact—for mental well-being, the current study takes a psychological approach. Studying the internal psychological antecedents that may support the mental health of Tunisian social entrepreneurs is the aim of this study. To do this, a conceptual model that takes into account external support (social support, institutional support), the perception of social influence, and personality traits (openness, self-confidence trait, and self-transcendence) has been put forth. The effects of business endeavors on society Studying the internal psychological antecedents that may support the mental health of Tunisian social entrepreneurs is the aim of this study. To do this, a conceptual model that takes into account external support (social support, institutional support), the perception of social influence, and personality traits (openness, self-confidence trait, and self-transcendence) has been put forth.The social impact of entrepreneurial endeavors to observe how they affect the social entrepreneur's general well-being and job happiness. Based on a broad sample of 250 social entrepreneurs from various sectors in Tunisia, structural equation modeling validated all of the model's hypotheses. The theoretical and managerial ramifications of the survey results were examined. The theoretical and administrative ramifications of the survey's findings were examined.